2013
DOI: 10.3389/fnbeh.2013.00189
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroscience of Face Processing and Identification in Eyewitnesses and Offenders

Abstract: Humans are experts in face perception. We are better able to distinguish between the differences of faces and their components than between any other kind of objects. Several studies investigating the underlying neural networks provided evidence for deviated face processing in criminal individuals, although results are often confounded by accompanying mental or addiction disorders. On the other hand, face processing in non-criminal healthy persons can be of high juridical interest in cases of witnessing a felo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 162 publications
0
6
0
1
Order By: Relevance
“…In emotion research anger is for instance operationalized in brain response differences during the perception of violent versus neutral images 11 . Another commonly used approach is assessing brain response differences during the perception of facial expressions contrasting neutral expressions with emotional ones, such as angry 12 , happy, fearful and sad 13 . Moreover, avoidance-approach paradigms have been utilized measuring the automatic action tendency responses to facial expressions while participants were instructed to avoid angry and approach happy faces 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In emotion research anger is for instance operationalized in brain response differences during the perception of violent versus neutral images 11 . Another commonly used approach is assessing brain response differences during the perception of facial expressions contrasting neutral expressions with emotional ones, such as angry 12 , happy, fearful and sad 13 . Moreover, avoidance-approach paradigms have been utilized measuring the automatic action tendency responses to facial expressions while participants were instructed to avoid angry and approach happy faces 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Several category-selective areas are found in the lateral and ventral visual cortex, such as the face-selective areas (fusiform face area, FFA, and occipital face area, OFA) [ 6 8 ] and the house-selective areas (parahippocampal place area, PPA, and transverse occipital sulcus, TOS) [ 9 , 10 ]. More recently, several studies have demonstrated that these category-selective areas respond not only to preferred objects but also to non-preferred objects [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there are several emerging applications based in face recognition in augmented reality, gaming, security, and so on [3] [4] [13] [14]. Face recognition is also studied by neuroscientists and psychologists to provide useful insights in how the human brain works [15]. In such applications, features extracted from images or videos present high dimensionality and the sample availability for machine learning is scarce, potentially leading to the known curse of dimensionality [16].…”
Section: Introductionmentioning
confidence: 99%